Feeding of small Neotropical felids (Felidae: Carnivora) and trophic niche overlap in anthropized mosaic landscape of South Brazil - Alcides Ricieri Rinaldi; Flávia Heloísa Rodriguez; Anderson Luiz Carvalho; Fernando Camargo Passos (Biotemas)
Understanding the diversity of a community and its dynamics is especially important in altered habitats such as agricultural fields, where this information can help biodiversity conservation programs. In an altered landscape of the interior Atlantic Forest, western Paraná State, Brazil (25º41’ to 25º20’S and 53º56’ to 54º35’W), samples (310) were collected and a total of 110 samples could be determined for some small Neotropical felids, including 39 Leopardus guttulus (oncilla), 38 L. wiedii (margay) and 33 Puma yagouaroundi (jaguarondi). The diets of these felids contained typical synanthropic prey such as Mus musculus in 44% (L. guttulus), 32% (L. wiedii) and 15% (P. yagouaroundi) of the total samples. This observation and the sample collection in agricultural places demonstrate that felids can use this anthropized landscape. The small mammals (<100 g) were more common in the diet of these species. Nevertheless, the correction factor was shown to have significant efficiency in correcting estimates of biomass ingested for two of the three species of felids, and we therefore recommend that these species be used in future studies. Even with this observed coexistence, the food niche of the three species showed a large overlap.